Converging crises: public interest journalism, the pandemic and public health - Melissa A Sweet; Megan Williams; Ruth Armstrong; Janine Mohamed; Summer May Finlay; Amy Coopes (Sax Institute, 2020)
Public interest journalism has faced a longstanding funding crisis, cutbacks of staff and resources, and closures of newsrooms. This crisis is a critical public health concern, and it has been exacerbated by the COVID-19 pandemic. At the same time, the pandemic has highlighted the important roles played by public interest journalism - including in addressing health equity issues. The pandemic has also highlighted the need to address structural weaknesses in the media industry, with concentration of media ownership and underfunding of public broadcasters leading to many communities being under-served and under-represented. The public health sector can make important contributions to developing and sustaining a robust, public interest journalism sector. Public health professionals and organisations can advocate for policy reform to support public interest journalism, and incorporate consideration of public interest journalism into advocacy, education, research and practice.